The Effect of Local Anesthesia on Dermatological Actions on Patient Comfort - Puguh Riyanto; Olivia Jovina Priyanto (Indonesian Journal of Global Health Research, 2025)
Local anesthesia is commonly used in a variety of dermatological procedures to reduce pain and improve patient comfort. However, some side effects can occur, including burning sensations, nausea, vomiting, dizziness, blurred vision, and even impaired consciousness. This study aimed to evaluate the effect of local anesthesia on patient comfort during dermatological procedures. The study was conducted at an aesthetic clinic in Semarang from 7 to 9 February, involving 20 patients (2 men and 18 women). This study uses a quantitative descriptive study with a cross-sectional approach to assess patient comfort and side effects after local anesthesia in dermatologic procedures. Patients aged 18 and older who consent will be recruited consecutively. Researchers will using observation checklist and vital sign chart to collect demographic and clinical data, observe and record specific side effects such as feeling hot/sore, nausea, vomiting, dizziness, blurred vision, impaired consciousness, and fainting during and up to 30 minutes after the procedure, and monitor vital signs before and after the procedure. The results showed that 16 out of 20 patients reported no complaints after the procedure. Three patients experienced a burning sensation, while one patient experienced nausea and vomiting. None of the patients reported dizziness, blurred vision, loss of consciousness, or fainting. In conclusion, local anesthesia provides a high level of comfort for patients with minimal side effects. Therefore, it remains a safe and effective option for dermatological procedures, although monitoring individual responses remains important.